Analisis Permasalahan Pembelajaran IPS Di Sekolah Dasar - Ridwan, Ridwan; Mulyana, Mulyana; Sarabunis, Fitri; Yusniar, Yusniar; Deliana, Intan; Syarfida, Syarfida; Riska, Raihan; Santi, Yulia (Alifbata : Jurnal Pendidikan Dasar, 2025)
This research aims to analyze the problems faced in learning Social Sciences (IPS) at UPTD SD Negeri 18 Peusangan. Based on initial observations, it was found that students' low interest and understanding of social studies subjects was influenced by the dominant learning method using lectures, limited learning media, and the lack of relevance of the material to students' lives. Apart from that, limited teacher competence in using technology and applying innovative methods is also a factor that contributes to this problem. This research method uses a qualitative approach, with data collection techniques through observation, interviews and analysis of student learning outcomes. The research results show that students are less motivated and passive during social studies learning because the method tends to be monotonous and the material is not linked to everyday experiences. Learning media that is limited to textbooks makes learning less interesting for students. The low scores on student learning outcomes indicate that they have difficulty understanding social studies material in depth. Solutions are needed in the form of implementing more interactive learning methods, using simple visual or digital media, and training for teachers in the use of technology and student-based learning methods.